Methoden van systematische rechtspraakanalyse Tussen juridische dogmatiek en data science - Verbruggen, Paul (Boom Uitgevers Den Haag, 2021)
Practitioner lawyers and legal scientists pay a lot of attention to providing insight into developments and patterns in the judiciary. However, with the question of exactly how they arrive at their insights and account for them, they are entering less familiar territory. Important questions they ask themselves are: How do I collect case law? Which statements do I select or not select for analysis? How do I expose a pattern? How reliable are the insights found? What exactly is their relevance and meaning? And how can software, artificial intelligence or other data science techniques help with this? Methods of systematic case law analysis addresses these and other questions that arise when conducting large-scale case law research. With the increasing digital availability of justice, this research is increasingly attractive. At the same time, this development justifies increased attention to the methodological justification of case law analysis. In this book, the authors outline some important methodological lessons for doing this type of legal research based on their experiences with systematic case law analysis. This makes the book important for students, PhD students and more experienced lawyers in science and practice.